Effect of dual-purpose summer legumes and zinc fertilization on system productivity, economics and nutrient use-efficiencies of rice (Oryza sativa) – wheat (Triticum aestivum) cropping system - JAT, S L; SHIVAY, Y S; PARIHAR, C M (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 2007-09 at the research farm of IARI, New Delhi, India; to study the effects of dual-purpose summer legumes and zinc fertilization in aromatic hybrid rice (Oryza sativa L.)– wheat (Triticum aestivum L.) cropping system. The higher system productivity, N and Zn uptake, nutrient-use efficiencies, net return and B:C ratio were recorded in cowpea [Vigna unguiculata (L.) Walp.] or mungbean (Vigna radiata L.) residue incorporated plots. The N balance was negative (-) in all treatments but it was least negative (-) in cowpea among summer treatments followed by mungbean. The highest N and Zn uptake, system productivity in terms of grain yield, i.e. 12.32 and 12.71 tonnes/ha was observed with application of 2.0% ZEU (ZnSO4.7H2O). Among the Zn fertilization treatments the lowest negative (-) balance of N was recorded with control (only N), i.e. -36.92 kg/ha in 2007-08 however in 2008-09 it was recorded with coating material coated urea, i.e. -39.54 kg N/ha over rest of the Zn treatments. The application of 5.0 kg Zn/ha (ZnO) gave the highest (2 696 and 2 601 g/ha during 2007-08 and 2008-09, respectively) positive Zn balance under rice-wheat cropping system. Partial factor productivity, agronomic efficiency, apparent recovery and physiological efficiency of applied N and Zn in rice-wheat cropping system were increased with Zn-enriched urea. The agronomic efficiency of N with 2.0% ZEU (ZnSO4.7H2O) increased by 49.7% and the N recovery efficiency in grain increased up to 57.6% over normal practice of prilled urea application. With the application of 2.0% ZEU (ZnSO4.7H2O) the agronomic efficiency of Zn increased in the range of 54 to 160% while Zn apparent recovery (%) in grain increased from 70 to 318% over 2.0% ZEU (ZnO) and 5.0 kg Zn/ha (ZnO), respectively. The dual-purpose summer legume incorporation in rice-wheat system gave higher net returns by 29 to 34% in 2007-08 and 42 to 45% during 2008-09 over summer fallow with B:C ratio up to 3.01. The application of 2.0% ZEU (ZnSO4.7H2O) gave the highest B:C ratio of 3.02 and increased net returns of aromatic-hybrid rice-wheat system by 11.6 to 12.2% over prilled urea application.